Correction: Nasiri et al. Impact of Policy Instruments in the Implementation of Renewable Sources of Energy in Selected European Countries. Sustainability 2022, 14, 6314 - Nasiri, Elnaz; Rocha-Meneses, Lisandra; Inayat, Abrar; Kikas, Timo (Sustainability, 2022)
The authors would like to make the following corrections about the published paper [...]